2021
DOI: 10.1016/j.petrol.2020.108134
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of oil recovery by emulsion injection: A pore scale analysis from X-ray micro-tomography measurements

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…We believe several of our observations to hold for 3D systems as well. Similar air cluster size distributions (Iglauer et al 2010(Iglauer et al , 2012Scheffer et al 2021) and a similar flow structure, displaying a clear separation of liquid flow in stagnation regions and preferential paths (Holzner et al 2015), have also been described in three-dimensional conditions. It has also been shown previously that the mixing dynamics in 3D unsaturated porous media follow the same scaling laws as in 2D unsaturated flows (Markale et al 2021).…”
Section: Discussionmentioning
confidence: 54%
“…We believe several of our observations to hold for 3D systems as well. Similar air cluster size distributions (Iglauer et al 2010(Iglauer et al , 2012Scheffer et al 2021) and a similar flow structure, displaying a clear separation of liquid flow in stagnation regions and preferential paths (Holzner et al 2015), have also been described in three-dimensional conditions. It has also been shown previously that the mixing dynamics in 3D unsaturated porous media follow the same scaling laws as in 2D unsaturated flows (Markale et al 2021).…”
Section: Discussionmentioning
confidence: 54%
“…However, following previous works that report a decrease in dispersivity once the system is desaturated below the so-called critical saturation (Raoof & Hassanizadeh, 2013), we hypothesize a decrease in the broadness of the velocity distribution through an increase in the dead-end area-PDF exponent γ for saturation degrees below that critical saturation. In addition, although the present study considers a high porosity (0.71), the distribution of nonwetting-phase cluster sizes still exhibits power-law behavior for porosity values as low as 0.11 (Iglauer et al, 2010(Iglauer et al, , 2012Scheffer et al, 2021). The effect of broader pore size variability (de Anna et al, 2017) under unsaturated conditions remains an important open question.…”
Section: Discussionmentioning
confidence: 83%
“…14 In the flooding process, it is very important that the oil-displacing agent employed can easily emulsify the crude oil and form a stable emulsion. 15,16 Bio-based emulsifiers have been widely used in biomedical, 17 agricultural, 18 food 19 and other fields due to their wide availability, low cost, and environmentally friendly nature. 20,21 These materials have the potential to be applied in EOR applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies have shown that the emulsification process, in particular, the formation of stable emulsions, could significantly enhance oil recovery. It has been demonstrated that the transport of emulsified droplets of residual oil through the pores within the formation has a positive impact on the displacement efficiency . In the flooding process, it is very important that the oil-displacing agent employed can easily emulsify the crude oil and form a stable emulsion. , …”
Section: Introductionmentioning
confidence: 99%